The reality of Saudi families’ support for distance education and the challenges they faced in times of disasters and crises “The Corona Virus Pandemic (COVID-19) as a Model” - Alotaibi, Wadha Habab (Journal of Educational and Psychological Sciences, 2023)
This research aimed at identifying the Saudi family's roles in supporting distance education, the reality of the Saudi family's performance of these roles and the challenges it faced in light of the emerging coronavirus pandemic. The sample of the research consisted of (801) respondents, (245) of which were teachers, leaders, supervisors, and educational faculty members, and (556) of them were students' parents. The results of the research showed that the research sample members of the educational staff agreed with that the family roles suggested by the research are important in in supporting the process of distance education. The results also showed that Saudi families perform their role in supporting distance education with a very high degree, and that (49.8%) of families reported that they did not face any challenges in supporting their children's learning, while the remaining families reported a number of challenges such as: the period in which the distance education was provided is inappropriate, the difficulty of devoted full-time to following up on children, the weak response of students, the interruption of the Internet, etc. In addition, the results showed that there is a statistically significant difference in the role of the Saudi family in supporting the process of distance education due to the variable of the type of parents in favor of mothers, and the absence of statistically significant differences due to the variable of the number of children and parents have a job.
Keywords: roles; Saudi family; distance education; coronavirus; challenges